The The Students’ Problems in Learning of Subject Verb Agreement Towards The Third Grade Students of University of Muhammadiyah Tangerang - Imtihan Hanim; Elsa Amelia; Firda Nurussalamah; Jihan Fadhillah; Lituhayu Rusfiyanti (Departement of Mathematics Education, 2024)
This study aims to find out the subject and verb writing errors made by students majoring in English Education at Universitas Muhammadiyah Tangerang when they complete paragraphs in verb form. Error analysis technique was conducted in this study to find the errors faced by the students in terms of present tense, identify the types of errors as well as the sources of errors. This study is descriptive research with 10 students participating in this study. The data of this study were collected from 1) students' writings focusing on students' sentences containing subject-verb agreement errors, and 2) interviews obtained from the students. The findings of this study are as follows: Subject and verb errors made by students cover form of information, omission, and addition errors, while from the point of view of linguistic categorization, the errors made by students are in the form of using singular plural nouns placed as subjects, improper use of verbs, and improper use of verbal and nominal sentences in making present tense sentences. The analyzed data also shows that students' errors in subject-verb agreement are classified as local errors. The cognitive strategies were chosen by them in comprehending the grammar